2021
DOI: 10.3390/ma14040722
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Single-Fiber Pull-Out of Polypropylene Fibers Produced with Different Mechanical and Surface Properties for Concrete Reinforcement

Abstract: In strain-hardening cement-based composites (SHCC), polypropylene (PP) fibers are often used to provide ductility through micro crack-bridging, in particular when subjected to high loading rates. For the purposeful material design of SHCC, fundamental research is required to understand the failure mechanisms depending on the mechanical properties of the fibers and the fiber–matrix interaction. Hence, PP fibers with diameters between 10 and 30 µm, differing tensile strength levels and Young’s moduli, but also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Commercial iPP‐1 bearing a reduced melt viscosity and crystallinity enabled a very smooth and even fiber surface, whereas our UHMW‐iPP with its ultrahigh molecular weight and increased crystallinity led to a high surface roughness induced by fibrillation. This high surface roughness is well known for UHMW‐PE fibers, especially for high draw ratios [11] . Surprisingly, annealing of the polymer fibers melted the fiber surface for all investigated fibers (Figure 2).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Commercial iPP‐1 bearing a reduced melt viscosity and crystallinity enabled a very smooth and even fiber surface, whereas our UHMW‐iPP with its ultrahigh molecular weight and increased crystallinity led to a high surface roughness induced by fibrillation. This high surface roughness is well known for UHMW‐PE fibers, especially for high draw ratios [11] . Surprisingly, annealing of the polymer fibers melted the fiber surface for all investigated fibers (Figure 2).…”
Section: Resultssupporting
confidence: 54%
“…This high surface roughness is well known for UHMW-PE fibers, especially for high draw ratios. [11] Surprisingly, annealing of the polymer fibers melted the fiber surface for all investigated fibers (Figure 2). Underneath that melted surface, the fibrillated structure was preserved for UHMW fibers (Figure 2, b).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…adopted from Curosu et al [5] SHCC micromechanics under impact is hence a crucial aspect to be considered towards the design of structural retrofitting components. To this aim, in-depth studies investigate the best engineered fibres to foster the overall dissipative capability of SHCC subjected to impact [6].…”
Section: Development Of Strain-hardening Cement-based Composites For ...mentioning
confidence: 99%
“…The workability reduced with increasing fiber content, although it was still in the permissible range. Wolfel et al [ 32 ] concluded from their study on various types of polypropylene fibers that the efficiency of the fibers could be enhanced by use of higher strength polypropylene fibers with increased surface roughness. Wang et al [ 33 ] studied the effect of various types of fibers on the crack resistance of concrete and reported improved resistance of the polypropylene fiber-reinforced concrete to cracking induced by restrained shrinkage.…”
Section: Introductionmentioning
confidence: 99%